Monitoring training loads in professional basketball players engaged in a periodized training program - Aoki, M. S.; Ronda, L. T.; Marcelino, P. R.; Drago, G.; Carling, C.; Bradley, P. S.; Moreira, A. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to investigate the dynamics of external training load (eTL) and internal training load (iTL) during seasonal periods, and examine the effect of a periodized training program on physical performance in professional basketball players. Repeated measures for 9 players (28 ± 6 years; 199 ± 8 cm; 101 ± 12 kg) were collected from 45 training sessions, over a 6-week preseason phase and a 5-week in-season phase. Physical tests were conducted at baseline (T1), week 4 (T2), and week 9 (T3). Differences in means are presented as % ± confident limits. A very likely difference was observed during in-season compared with preseason for the eTL variables (measured by multivariable monitoring device), mechanical load (13.5 ± 8.8) and peak acceleration (11.0 ± 11.2), respectively. Regarding iTL responses, a very large decrement in TRIMP (most likely difference, -20.6 ± 3.8) and in session rating of perceived exertion training load (very likely difference, -14.2 ± 9.0) was detected from preseason to in-season. Physical performance improved from T1 to T3 for Yo-Yo intermittent recovery test 1 (62.2 ± 34.3, effect size [ES] > 1.2); countermovement jump (8.8 ± 6.1, ES > 0.6); and squat jump (14.8 ± 10.2, ES > 0.8). Heart rate (HR; %HRpeak) exercise responses during a submaximal running test decreased from T1 to T3 (3.2 ± 4.3, ES < 0.6), as well as the HR recovery after the test (14.7 ± 8.8, ES > 1.2). These results provide valuable information to coaches about training loads and physical performance across different seasonal periods. The data demonstrate that both eTL and iTL measures should be monitored in association with physical tests, to provide a comprehensive understanding of the training process.